The media-preferences of the population of Central Asian countries: the results of sociological research - Alimbekova, Gulzhan T.; Shabdenova, Aizhan B. (Journal of the Belarusian State University. Sociology, 2019)
In order to study the post-Soviet space in various countries established research institutes and centers, but still not enough data and first-hand information about the various aspects of life in these countries. In particular, it is interesting to study the media preferences of the population of Central Asia: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan, despite the common Soviet past, each of these countries has its own unique path of development and its features, including access to external information. This article presents some results of sociological surveys of mentioned countries’ population in terms of their media preferences. The purpose of this longitudinal study was to explore public opinion on a range of social and political issues. Achieving the goal of the study was determined by the tasks of studying the level of satisfaction of the population with the work of various structures, the assessment of certain events, the situation in the country, the social well-being of residents. In addition, we identified the most common sources of information, trends in access to external information. Comparative analysis of the results showed that despite of increase of communication technologies, the most important source of information in these countries is the television. The study showed the importance of information sources in each of the studied countries, as well as the most preferred TV channels, radio, newspapers and Internet sources. In the households of the countries, the presence of only national TV channels is gradually reduced and cable or satellite TV is expanding, the predominance of only national TV channels is more widespread among the citizens of Uzbekistan.
Keywords: media preferences; media; Central Asia; media space